Mutually exclusive alternative pre-mRNA splicing promotes adaptive metabolic stress signaling by JNK - Alexandra Lee; Autumn Gentzler; Declan Fitzpatrick; Sithara Raju Ponny; Ozkan Aydemir; Myoung Sook Han; Caroline A. Lewis; Guangping Gao; Roger J. Davis (Proceedings of the National Academy of Sciences, 2026)
The JUN NH 2 -terminal kinase (JNK) signal transduction pathway is activated during the hepatic metabolic stress response. The JNK1 and JNK2 pre-mRNAs expressed by hepatocytes exhibit mutually exclusive inclusion of exons 7a or 7b that encode a segment of the substrate binding site that is required for selective protein phosphorylation. We established mice with conditional inclusion of exons 7a or 7b to test the function of these JNK spliceoforms. We report that the JNK2 7b spliceoform plays a key role in the hepatic metabolic stress response. This function of JNK2 7b is mediated by coordinated mechanisms that independently regulate circadian gene expression and phosphorylation of Retinoid X Receptor α (RXRα) on Ser 265 . This analysis identifies an important role for JNK2 7b in the hepatic adaptive response to metabolic stress.